Fungsi Makna Semiotika Pada Tradisi Tingkeban Dalam Kehidupan Masyarakat Jawa Sidodadi Kecamatan Beringin Lubuk Pakam - Tuti Rahmadani; Rosmilan Pulungan (LPPM STIKes SITI HAJAR dan Insight Power, 2021)
In Javanese society, transitional ceremonies are carried out in the event of birth, marriage, and death. This paper will lift the ceremony that is included in the birth event. Tingkeban is a monthly even-day ceremony performed by pregnant women. The series of these ceremonies include flushing and slametan. In slametan ceremony contained meaning in symbols in the form of symbols, symbol functions and symbol meanings, this is the object of the author's research to describe the shape of the symbol, the function of the symbol and the meaning of the symbol in the Tingkeban ceremony procedure. This research uses qualitative research methods that are descriptive by collecting data through observation and interviews. Informants both involved and who are considered to understand about the tradition, namely public figures and books that support this research as a source of data. This observation was made on the value of symbolism in the form, meaning, and function of each procession or equipment in the community in Sidodadi District Beringin Lubuk Pakam, so that the values of symbolism were found to be the material of research. In this study used the approach of Clifford Geertz Theory. In addition, it also uses research on the value of the study of symbolism. The results of this study have three types based on its purpose, namely judging from the form of traditional ceremonies performed by someone who is blessed with a baby in his womb that is already seven months old. The study of symbolism of tingkeban procedures in the Javanese sidodadi community of Beringin Lubuk Pakam subdistrict includes 1) Description of the shape of the symbol, 2) description of the meaning of the symbol, and 3) description of the function of the symbol. Based on the above research, it is expected that researchers can further develop research on the procedure of tingkeban (seven months pregnant), using an approach so as to find new things that are interesting. For the world of education, it is hoped that the results of the research can contribute ideas to the understanding of literary works, especially those related to the teaching of literature and culture, and also the procedures for ceremonial processions for people who are seven months pregnant. In addition, it can be used as an encouragement for students and students to pay more attention to the study of symbolism in traditions or ceremonies in society. Keywords: Symbolic Meaning, Tradition, Javanese Tingkeban